2016
DOI: 10.1007/s40808-016-0119-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of urban heat island intensity under urban–suburban surface and reference site in Kolkata, India

Abstract: Urban heat island intensity (UHII) in Kolkata has been assessed using simplified numerical model for vertical temperature measurement in tropical monsoon summer month (June, 2015) during pre-onset of monsoon season. The data of 25 field observation sites show that the surface temperature curves are likely to mathematical trapeziums, and surface temperatures are related to vertical air temperatures. Therefore, approximated temperature trapeziums that are determined by high and lower air temperatures can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We focus our simulations on hot, pre‐monsoon days characterized by considerable urban heating and associated health risk. Extreme heatwaves aggravate conditions in urban areas by boosting temperatures within the built environment and increasing urban temperatures more intensely than rural temperatures (Khan & Chatterjee, 2016; Khan, Akbari, et al., 2022). Under such adverse weather conditions, mitigation strategies are critically needed to reduce peak ambient temperatures and minimize any heat‐related health risks.…”
Section: Methodsmentioning
confidence: 99%
“…We focus our simulations on hot, pre‐monsoon days characterized by considerable urban heating and associated health risk. Extreme heatwaves aggravate conditions in urban areas by boosting temperatures within the built environment and increasing urban temperatures more intensely than rural temperatures (Khan & Chatterjee, 2016; Khan, Akbari, et al., 2022). Under such adverse weather conditions, mitigation strategies are critically needed to reduce peak ambient temperatures and minimize any heat‐related health risks.…”
Section: Methodsmentioning
confidence: 99%
“…IMDAA is a regional atmospheric reanalysis over the Indian subcontinent with a horizontal resolution of about 12 km [76]. The fifth-generation reanalysis popularly known as ERA-5 (spatial resolution ~31 km), released by ECMWF, is an upgraded version of Era-Interim (spatial resolution ~79 km) in terms of spatial resolution [77]. In this data quality test, we chose three stations, namely Alipore (Kolkata), Diamond Harbour, and Darjeeling.…”
Section: Importance Of Data Quality In Estimating Human Bioclimate Co...mentioning
confidence: 99%
“…Similarly, respiratory and lung diseases are related to high ozone levels induced by heat events. Studies (Pickett et al, 2008;Khan and Chatterjee 2016) carried out in several cities of the United States such as Atlanta, New York, Chicago, and Washington, have shown that urbaninduced precipitation and thunderstorm events are mainly initiated by the UHI. Other meteorological impacts of the UHI are associated with reductions in snowfall frequencies and intensities, as well as reductions in the diurnal and seasonal range of freezing temperatures.…”
Section: Urban Heat Islands -Effectsmentioning
confidence: 99%